LIVED EXPERIENCES OF TERTIARY PHYSICAL EDUCATION TEACHERS IN QUARANTEACHING (Malaysian Journal of Learning and Instruction, 2022)
The inclusion of physical education in the curriculum in the new normal, and with the mandate on the adoption of flexible learning at the tertiary level caused by the Covid-19 pandemic forced physical educators to do quaranteaching or teaching in the quarantine. This study described the lived experiences of physical education (PE) teachers in quaranteaching utilizing Edmund Husserl’s phenomenological qualitative research design. A total of seven PE teachers from two universities participated in this study which achieved data saturation. Anchored to Colaizzi’s phenomenological approach and guided by different philosophies, data were analyzed and presented in two prong clustering. The results revealed that tertiary PE teachers experienced difficulties and yet learnt to innovate in terms of teaching the course, assessing, monitoring, and giving feedback to students, dealing with the internet and technology, and handling physical and cognitive situations. It is recommended that tertiary PE teachers undergo pedagogical and technological trainings and workshops especially in the utilization of different learning platforms to help them improve their pedagogy and in the innovative use of digital tools and technologies to teach PE in the new normal. digitalinessPurpose - The sudden shift from face-to-face to online learning compelled educators including physical educators to teach PE in the midst of quarantine, with no face-to-face interaction. This study described the experiences of tertiary PE teachers in teaching PE in the quarantine.Methodology - The study utilized the descriptive phenomenological qualitative research design by Edmund Husserl. The participants were seven PE teachers from two state universities in Cebu, Philippines, selected through purposive snowball sampling. Data gathered were analyzed through Colaizzi’s approach of data analysis and presented in two prong clustering.Findings - The study revealed that the experiences of tertiary PE teachers in teaching PE during quarantine can be described under two classifications. They experienced difficulties and yet learnt to innovate in terms of teaching the course, assessing, monitoring, and giving feedback to students, using the internet and technology, and handling physical and cognitive situations.Significance - The study has provided a better understanding of PE teachers by revealing their challenges, struggles, needs, strengths and weaknesses in quaranteaching. Results of the study could serve as a basis for implementing trainings, workshops and webinars related to pedagogy and technology enhanced learning to assist PE teachers in teaching in the new normal.